Maternal Knowledge of Exclusive Breastfeeding and Nutritional Status of Children Under Two Years During the COVID-19 Pandemic - Fairuz SMW, Amirra; Fadilah, Tubagus Ferdi (CoinReads Media Prima, 2025)
Introduction: Breast milk is the ideal source of nutrition for infants, especially during the first six months of life, as it supports optimal growth and development. A mother's knowledge of exclusive breastfeeding plays a crucial role in ensuring a child's nutritional status. Insufficient maternal knowledge can negatively impact breastfeeding practices and lead to poor nutritional outcomes. According to the World Health Organization (WHO), 161 million children under five experienced nutritional deficiencies globally in 2014. Disruptions in healthcare services during the COVID-19 pandemic further exacerbated these challenges, making it more difficult for mothers to access the information and support they needed for successful breastfeeding. Methods: This cross-sectional analytic observational study was conducted at Posyandu Cempaka A and B in Tanah Baru sub-district, Bogor City, during the COVID-19 pandemic. A total of 53 mothers with children under two years old were selected using consecutive non-random sampling. Data were collected through validated questionnaires assessing maternal knowledge of exclusive breastfeeding and direct anthropometric measurements of the children. Data were analyzed using Fisher's exact test. Results: The study found a significant relationship (p = 0.038) between maternal knowledge of exclusive breastfeeding and the nutritional status of children under two years old. Mothers with better knowledge were more likely to have children with normal nutritional status. Conclusion: Maternal knowledge of exclusive breastfeeding is significantly associated with the nutritional status of children under two years old, even during the COVID-19 pandemic. These findings highlight the importance of maternal education to improve child health outcomes.